2007
DOI: 10.1533/ijcr.2006.0134
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations of motorcycle helmet impact tests

Abstract: The main objective of this study was to simulate experimental impact tests on a commercially available motorcycle helmet and to develop a virtual design tool. The mechanical properties of the shell and the foam liner of the helmet were estimated from existing material data taken from the open literature. The material data were adjusted to match the temperature conditioning of each impact test condition. All computational impact tests were performed using the explicit finite element code LS-DYNA3D with appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…A comparison, of compression tests on a complete shell with FEA of the same loading geometry, showed that the Young's modulus of the GRP in the Mavet helmet was relatively low. This is almost certainly true for other helmets, suggesting that the moduli used in [11] and [12] were probably too high. GRP fracture and delamination does not occur in the flat anvil impacts, so these phenomena were not modelled.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A comparison, of compression tests on a complete shell with FEA of the same loading geometry, showed that the Young's modulus of the GRP in the Mavet helmet was relatively low. This is almost certainly true for other helmets, suggesting that the moduli used in [11] and [12] were probably too high. GRP fracture and delamination does not occur in the flat anvil impacts, so these phenomena were not modelled.…”
Section: Discussionmentioning
confidence: 99%
“…GRP fracture and delamination does not occur in the flat anvil impacts, so these phenomena were not modelled. However, to model impacts on kerbstone anvils, these phenomena should be included in the FEA, as in [12]. If FEA is to replace prototype testing, in developing helmet designs to pass EC Regulation 22 or BS 6658, it is vital to model all the main protective foam components; the cheek pad foam was loaded in impacts at the helmet side, and the chin bar centre foam was loaded in frontal impacts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its ease of calibration and accuracy in single impact events, these models are used in many studies where the focus is primarily on simulating shell material behaviour accurately such as in [40], [21] and [1].…”
Section: Materials Modelsmentioning
confidence: 99%
“…Aiello et al [1] modelled contact between the outer shell and inner foam liner by defining a 'tiebreak' interface condition. This contact condition bonds the surfaces of two solid or surface meshes and prevents any sliding or separation between the surfaces.…”
Section: Impact Modellingmentioning
confidence: 99%